Hypothermia improves neuronal network recovery in a human-derived in vitro model of oxygen-deprivation. - Eva J H F Voogd; Marloes Thijs; Marloes R Levers; Jeannette Hofmeijer; Monica Frega (PLoS ONE)
Mild therapeutic hypothermia showed potential neuroprotective properties during and after cerebral hypoxia or ischemia in experimental animal studies. However, in clinical trials, where hypothermia is mainly applied after reperfusion, results were divergent and neurophysiological effects unclear. In our current study, we employed human-derived neuronal networks to investigate how treatment with hypothermia during hypoxia influences neuronal functionality and whether it improves post-hypoxic recovery. We differentiated neuronal networks from human induced pluripotent stem cells on micro-electrode arrays (MEAs). We studied the effect of hypothermia (34°C)-as well hyperthermia (39°C) - on neuronal functionality during and after hypoxia using MEAs. We also studied the effects on the number of synaptic puncta and cell viability by immunocytochemistry. In comparison to neuronal networks under normothermia, we found that hypothermia during hypoxia improved functional neuronal network recovery, expressed as enhanced neuronal network activity. This was associated with prevention of synaptic loss during and after the hypoxic phase. Furthermore, hypothermia improved cell viability after the hypoxic phase. Instead, hyperthermia during hypoxia had detrimental effects, with an irreversible loss of neuronal network function, loss of synaptic puncta and decreased cell viability. Our results show potential neuroprotective properties of hypothermia occurring during hypoxia, indicating that administering hypothermia to bridge the time to reperfusion may be beneficial in clinical settings.